2011
DOI: 10.1210/jc.2010-1878
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass in Subjects with Klinefelter Syndrome: Role of Testosterone Levels and Androgen Receptor Gene CAG Polymorphism

Abstract: Testosterone levels and AR CAG polymorphism are not associated with bone mass phenotype in KS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 37 publications
(41 reference statements)
4
41
0
2
Order By: Relevance
“…However, acute testosterone deprivation in healthy men leads to an increase in serum CCL2 levels, which is not reversed by restoration of physiological circulating concentrations of testosterone. Furthermore, the differences in the response to testosterone replacement therapy in KS could be dependent upon androgen receptor polymorphism (16,17,18). These results suggest that, in addition to hormonal factors, a genetic predisposition, possibly mediated through macrophage infiltration into adipose tissue, is involved in the development of MS in KS (15).…”
Section: Metabolic Syndromementioning
confidence: 88%
“…However, acute testosterone deprivation in healthy men leads to an increase in serum CCL2 levels, which is not reversed by restoration of physiological circulating concentrations of testosterone. Furthermore, the differences in the response to testosterone replacement therapy in KS could be dependent upon androgen receptor polymorphism (16,17,18). These results suggest that, in addition to hormonal factors, a genetic predisposition, possibly mediated through macrophage infiltration into adipose tissue, is involved in the development of MS in KS (15).…”
Section: Metabolic Syndromementioning
confidence: 88%
“…[ Salbenblatt et al, 1985;Lanfranco et al, 2004;Ferlin et al, 2011b], whereas others found reduced E2 concentrations [Aksglaede et al, 2007a].…”
Section: Article American Journal Of Medical Genetics Part C (Seminarmentioning
confidence: 98%
“…Accordingly, adults with XXYoften present with decreased bone mineral density (BMD) [Horowitz et al, 1992;Bojesen et al, 2010;Aksglaede et al, 2011b;Ferlin et al, 2011b] In contrast to the studies on adults with XXY, normal lumbar BMD, and whole body bone mineral content (BMC) as evaluated by whole body DEXA scan in 24 boys and adolescents with XXY (4.3-18.6 years of age) has been shown, indicating that the risk of osteopenia/osteoporosis may not be present until after puberty [Aksglaede et al, 2008a].…”
Section: Bone Mineralizationmentioning
confidence: 99%
“…Our data in KS do not confirm this result. Although further studies are necessary to clarify these aspects, it has to be noted that the effect of testosterone on prostate growth and the role of CAG repeat length in modulating the effects of testosterone in KS are still controversial (17,19,36).…”
Section: Discussionmentioning
confidence: 99%
“…The AR gene is located on the X chromosome, and therefore in KS, it is present in double copy. The inactivation rate of the two X chromosomes, and the effective CAG repeat value in heterozygous KS men, was calculated as an X-weighted biallelic mean (19). This analysis was based on methylation-specific PCR at the human AR locus, with primers spanning the (CAG)n polymorphism region, as described previously (20).…”
Section: Patients and Clinical Analysismentioning
confidence: 99%